2009
DOI: 10.3199/iscb.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetical effects of some mycotoxins to chromosomes of Triticum durum using RAPD-PCR fluorescence in situ hybridization

Abstract: ABSTRACT. PCR-amplified DNA using the random primer OPB-06 was used as a probe for Fluorescence in situ hybridization (FISH). Signals of hybridized sites were observed in both interphase and metaphase plates after hybridization. The FISH signals of the metaphase chromosomes were confirmed as two yellow-color signals hybridized with the probe on two adjacent loci at interphase of the control plates. FISH analysis of the metaphase plates of 25µg/ml deoxynivlenol (DON) and aflatoxin B 1 (AFB 1 ) treated plants re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In contrast, rDNA FISH gives much higher resolution for detecting chromosome variations among closely related species. Our present results and other studies (Kondo et al 1996;Honda et al 1997;Abd El-Twab and Kondo 2003, 2007, 2008, 2009) have shown that the number and positions of major rDNA sites on chromosomes varied among the closely related genera and even species. This variation should have a phylogenetic implication, since the more similar rDNA FISH patterns are likely to be in the most closely related taxa (Abd El-Twab and Kondo 2003).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…In contrast, rDNA FISH gives much higher resolution for detecting chromosome variations among closely related species. Our present results and other studies (Kondo et al 1996;Honda et al 1997;Abd El-Twab and Kondo 2003, 2007, 2008, 2009) have shown that the number and positions of major rDNA sites on chromosomes varied among the closely related genera and even species. This variation should have a phylogenetic implication, since the more similar rDNA FISH patterns are likely to be in the most closely related taxa (Abd El-Twab and Kondo 2003).…”
Section: Resultssupporting
confidence: 74%
“…In higher eukaryotes, rDNA's are organized into two distinct gene classes of the major rDNA cluster encoding 45S rDNAs and the minor rDNA cluster encoding 5S rDNAs, which are usually found in loci that are separated from those of the major rDNAs and are not involved in the nucleolus formation (Inafuku et al 2000;Abd El-Twab and Kondo 2002, 2006, 2007, 2009. Fluorescence in situ hybridization (FISH) allows identification of specific sequences in a structurally preserved cell, in metaphase or interphase.…”
Section: Abstract: Achillea Fragrantissima Chromosomes Dapi Fishmentioning
confidence: 99%
See 1 more Smart Citation